(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2011)
We present a case study whose main goal was to explore the relationship between therapeutic alliance´s ruptures and the client’s verbal expression of needs in psychotherapy. We intensively analyzed an unsuccessful case of a client with Panic Disorder with Agoraphobia. The sessions were analyzed using the Ruptures Resolution Rating System (3R’s) and the Sistema de Observação de Responsividade Terapêutica . The results indicate that an increase in the Verbal Expression of Needs (EVN) is associated with a decrease of the ruptures three and four sessions later and that an increase in ruptures is associated with an increase of EVN four sessions later. There was a more clear association between the confrontation ruptures, particularly the expression of dissatisfaction about therapeutic activities, and a specific type of EVN:the client´s expression of direct requests related to therapy.